Chapter Da La celosa de sí misma di Tirso a La gelosa di se stessa, melodramma di Arcangelo Spagna - Trecca, Simone (Studi e saggi, 2020)
La gelosa di se stessa is the fourth of the six melodramas collected in 1709 by Arcangelo Spagna and published in Rome (Domenico Antonio Ercole), as the third volume of his librettos, but its writing dates back to at least 1689, the date of a previous printed edition, shortly after the opera appeared on stage, a few months before at the palace at the Quattro Fontane of the Prince of Palestrina. It is not to be excluded, however, and this is dealt with in the first pages of this essay, the existence of still earlier editions, especially if we compare the two printed texts, already very divergent between them, and the two manuscripts, both at the Vatican Apostolic Library, to which the manuscript of the score must certainly be added for further problematization. The second section of this paper gets to the heart of the theme that interests us most here, namely the examination of Spagna's adaptive interventions with respect to what undoubtedly represents its main hypotext, Tirso de Molina's La celosa de sí misma. The analysis is conducted on the latest printed edition of the melodrama, to be considered as the version that the author wanted to pass on to posterity, as the authorized literary text, still intervening much compared to the previous edition of 1689 on which perhaps, being more linked to the stage event, he hadn't had much control.